The Development of Interactive E-LKPD Using Wizer.Me On Polyhedron For The Eighth Grade Students - Annisa Rahman Navira, Deva; Susanto, Susanto; Yudianto, Erfan; Suwito, Abi; Nur Safrida, Lela (Program Studi Pendidikan Matematika Universitas PGRI Kanjuruhan Malang, 2025)
This research aims to develop an Electronic Student Worksheet (E-LKPD) using the Wizer.Me platform for teaching polyhedron material that meets the criteria of validity, practicality, and effectiveness. The study employed a Research and Development (R&D) approach with the ADDIE model. The E-LKPD was designed based on a guided discovery learning model to help students better understand polyhedron concepts, their interconnections, and applications. Learning activities include matching polyhedron shapes with their names and discovering formulas through the “fill on image” feature in exploration tasks. The research was conducted at SMPN 1 Ledokombo, Jember, involving eighth-grade students as participants. Validation results show that the E-LKPD achieved a validity score (Va) of 3.84, indicating a valid category. The practicality level reached 82%, as evidenced by student response questionnaires, reflecting positive usability and engagement. Furthermore, the E-LKPD demonstrated effectiveness, with 34 out of 43 students achieving classical mastery, meaning more than 75% met the minimum learning standard. These findings indicate that the developed E-LKPD using Wizer.Me effectively supports students’ conceptual understanding and learning outcomes in polyhedron material, providing a valid, practical, and efficient digital learning tool for mathematics education.